NGUY CƠ HOANG MẠC HÓA Ở TỈNH ĐIỆN BIÊN - Lê, Trần Chấn (2016)
This paper presents analytical results of research into the status of local water resources and hydrological regimes of follows and river basins and the dynamic patterns connecting underground water, soil, topography, vegetation and climate. Based on calculations, Dien Bien province has 4 areas: the area facing a very high danger of desertification (occupying 14.8% of the province’s area); another area facing a medium desertification danger (47.22%); that facing only a weak desertification danger (30.11%); and the relatively small area facing no such danger (7.87%). The research outcomes are expected to contribute to understanding of the process of desertification in Dien Bien Province.